International variation in breast cancer incidence and mortality in young women - Sopik, Victoria (Breast cancer research and treatment, 2021)
Purpose Breast cancer in young women (< 40 years) is rare and carries a poor prognosis relative to breast cancer in older women. Most studies examining global breast cancer patterns do not describe the trends in young women specifically. Methods Data from GLOBOCAN 2018 were used to compare breast cancer incidence and mortality rates among younger (ages 0–39) vs. older (ages 40+) women across 185 countries. The coefficient of variation (the ratio of the standard deviation to the mean) was used to quantify relative variability. Results The risk of developing breast cancer to age 39 ranged from 0.13% in Guinea to 0.95% in South Korea (coefficient of variation: 46%), and the risk of death from breast cancer to age 39 ranged from 0.02% in China to 0.72% in Cameroon (coefficient of variation: 81%). In contrast, the risk of developing breast cancer to age 74 ranged from 1.5% in Mozambique to 12.2% in Belgium (coefficient of variation: 50%), and the risk of death from breast cancer to age 74 ranged from 0.65% in South Korea to 3.0% in Somalia (coefficient of variation: 36%). Conclusions Among young women, breast cancer mortality rates varied more worldwide than breast cancer incidence. In contrast, among older women/women of all ages, breast cancer incidence varied more than breast cancer mortality. Further research is required to examine the impact of stage at diagnosis, clinicopathologic features, and treatments received, on variations in the survival and mortality of breast cancer in young women around the world.